1965
DOI: 10.1152/ajplegacy.1965.208.5.1021
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hypoxia on secretion of ACTH in the rat

Abstract: Body weights, organ weights, and blood and pituitary ACTH concentrations were determined in rats exposed continuously to 20.9, 15.0, or 10.0% O2 atmospheres at normal barometric pressure for periods ranging from 3 to 120 hr. Hypoxia resulted in some loss of body weight, and loss of weight of the thymus and the ovary. The weight of the adrenals increased. Blood ACTH rose rapidly after exposure to hypoxic conditions, remaining elevated for the duration of the experiment. Control animals (20.9% O2) placed in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
11
0

Year Published

1975
1975
1999
1999

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 0 publications
3
11
0
Order By: Relevance
“…1 We noticed weight loss and haematocrit increase, 3 but not glandular hypertrophy, in rats after hypoxic stress for 3 weeks. Marks et al observed an increased adrenal weight in rats after hypoxic stress for 5 days.…”
Section: Resultsmentioning
confidence: 68%
See 4 more Smart Citations
“…1 We noticed weight loss and haematocrit increase, 3 but not glandular hypertrophy, in rats after hypoxic stress for 3 weeks. Marks et al observed an increased adrenal weight in rats after hypoxic stress for 5 days.…”
Section: Resultsmentioning
confidence: 68%
“…Marks et al observed an increased adrenal weight in rats after hypoxic stress for 5 days. 1 We noticed weight loss and haematocrit increase, 3 but not glandular hypertrophy, in rats after hypoxic stress for 3 weeks. Perhaps, hypoxic stress of rats for more than 5 days may induce alternative adaptation mechanisms that could offset the trophic effect of ACTH.…”
Section: Resultsmentioning
confidence: 68%
See 3 more Smart Citations